Determinants of Quality of Life on Persons with Physical Disability: Literature Review - Wina Al Syifa; Ella Nurlaella Hadi (Journal of Social Research, 2023)
People with physical disabilities not only have functional limitations but also have more risks related to health problems and social barriers faced than non-disabled people. Studies have shown that people with disabilities tend to have a low quality of life. The purpose of this study was to determine the determinants of quality of life in people with physical disabilities. The study design used literature review by analyzing articles that discuss the determinants of quality of life of people with physical disabilities. Article searches were conducted on three databases including Scopus, EBSCOhost and Google Scholar with the keywords Determinants, Quality of Life, and Physical Disability. Articles used in Indonesian and English with a time span between 2012 and 2022. Searching articles using keywords on Scopus found 176 articles, 57 articles on EBSCOhost Medline and 210 articles from Google Scholar. Furthermore, screening was carried out so as to produce 9 articles that are relevant and in accordance with the objectives of this literature review. The results found that gender, age, degree of disability, availability of assistive devices, access to health information, psychological factors, family support, social support and stigma and accessibility are determinants of quality of life of physical disability. Knowledge of the determinants of quality of life for people with physical disabilities can help health workers and relevant agencies to design interventions and provide appropriate support for them.